Distance to treatment as a factor for loss to follow up of hepatitis C patients in North East England. (23rd October 2018) - Simpson, H; Manley, P; Lawler, J; Morey, S; Buchanan, E; Hewett, M; Knowles, J; Miller, C; McCarron, B; Valappil, M; McPherson, S
Abstract: Background: A large proportion of the 200 000 HCV-infected individuals in the UK are undiagnosed or lost to follow-up. Engaging known infected individuals in treatment is essential for elimination. Methods: Using PHE surveillance data and HCV treatment registers from North East of England (NE) treatment centres for 1997–2016, we estimated the number of HCV cases not linked to treatment and the proportion with active infection. We compared distances of treated and untreated cases to treatment services, and assessed the effect of expanding HCV treatment into existing drug and alcohol treatment centres in the NEE on treatment accessibility. Results: The odds of being treated was associated with distance to treatment services. Confirmatory results for 50% were not reported to PHE NE. Overall, 3385 patients reported to PHE NE had no record of treatment; we estimated 1621 of these may have been lost to follow-up after confirmation of active infection. Conclusions: Poor access to healthcare services may contribute to under-diagnosis or loss to follow-up. Expanding HCV treatment delivery into NEE drug and alcohol treatment centres would improve the accessibility of treatment services to people infected with/at risk of HCV. This may increase the proportion receiving treatment and support progress towards elimination.